2012
DOI: 10.1100/2012/572514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Supplementation on the Distribution Patterns of Zinc, Copper, and Magnesium in Rabbits Exposed to Prolonged Cadmium Intoxication

Abstract: The present study is designed to investigate whether magnesium (Mg) supplementation may prevent Cd-induced alterations in zinc (Zn), copper (Cu), and magnesium (Mg) status in rabbits. For this purpose, the concentrations of Zn, Cu, and Mg were estimated in blood, urine, and organs (brain, heart, lungs, liver, kidney, spleen, pancreas, skeletal muscle, and bone) of rabbits given Cd (10 mg/kg b.w.) and rabbits cotreated with Mg (40 mg/kg b.w.) orally, as aqueous solutions of Cd chloride and Mg acetate every day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
2
12
0
1
Order By: Relevance
“…We further found an inverse correlation between dietary Mg intake and urinary Cu levels among the e-waste recyclers. This nding supports the results of Bulat et al (2012), who reported that Mg supplementation had profound effect on Cu status in cadmium-exposed animals. We also found a direct relationship between Mg intake from diet and Fe levels in the blood.…”
Section: Relationship Between Dietary Micronutrient Intake and Micronsupporting
confidence: 92%
“…We further found an inverse correlation between dietary Mg intake and urinary Cu levels among the e-waste recyclers. This nding supports the results of Bulat et al (2012), who reported that Mg supplementation had profound effect on Cu status in cadmium-exposed animals. We also found a direct relationship between Mg intake from diet and Fe levels in the blood.…”
Section: Relationship Between Dietary Micronutrient Intake and Micronsupporting
confidence: 92%
“…However, under our experimental conditions, the applied Cd dose of 10 mg kg -1 bw did not induce significant changes in the Cu and Mg content, although a significant decrease was achieved for Zn (43). No beneficial effect of Zn supplementation on the content of bioelements in bone was confirmed.…”
Section: Bulat Z Et Al Can Zinc Supplementation Ameliorate Cadmium-mentioning
confidence: 70%
“…The results on bioelement concentrations in the blood and organs of animals treated with Cd have already been published (43).…”
Section: Statistical Analysesmentioning
confidence: 90%
See 1 more Smart Citation
“…Increasing the rate of calcium, may present that cadmium has influenced on the bone metabolism and by destroying it, has caused to releasing magnesium ion from the skeleton tissue that finally results in increasing magnesium plasma concentration. It seems there is a competition between zinc and magnesium which caused to decrease magnesium in blood [24][25][26]. The results shows that zinc can neutralize the poisonous effect of cadmium, because magnesium has interfered in the most enzymes reactions such as kinases and phosphatases, and cadmium by its toxic effect on the synthesis may prevent the synthesis and releasing magnesium in the circulation, and zinc may neutralize the cadmium poisonous effects by its biologic effect and competing with cadmium.…”
Section: Discussionmentioning
confidence: 77%